2009
DOI: 10.1007/bf03178640
|View full text |Cite
|
Sign up to set email alerts
|

Effects of collimator backscatter in an Elekta linac by Monte Carlo simulation

Abstract: The effects of radiation backscattered from the secondary collimators into the monitor chamber in an Elekta linac (producing 6 and 10 MV photon beams) are investigated using BEAMnrc Monte Carlo simulations. The degree and effects of this backscattered radiation are assessed by evaluating the changes to the calculated dose in the monitor chamber, and by determining a correction factor for those changes. Additionally, the fluence and energy characteristics of particles entering the monitor chamber from the downs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…In Elekta linacs, however, there is a backscatter plate which prevents particles from the downstream direction entering the monitor chamber. It was shown that with the backscatter plate in place the proportion of particles backscattered into the monitor chamber is less than 0.35% and, therefore, corrections for field size dependence in monitor chamber dose are not necessary when running MC simulations of the Elekta linac. Moreover, since jaw opening is kept constant for all cone sizes, backscattering into the monitor chamber will not influence the calculation of ROF for stereotactic cones.…”
Section: Discussionmentioning
confidence: 99%
“…In Elekta linacs, however, there is a backscatter plate which prevents particles from the downstream direction entering the monitor chamber. It was shown that with the backscatter plate in place the proportion of particles backscattered into the monitor chamber is less than 0.35% and, therefore, corrections for field size dependence in monitor chamber dose are not necessary when running MC simulations of the Elekta linac. Moreover, since jaw opening is kept constant for all cone sizes, backscattering into the monitor chamber will not influence the calculation of ROF for stereotactic cones.…”
Section: Discussionmentioning
confidence: 99%
“…Various authors have quantified the backscatter into the monitor chamber [10,[20][21][22][23]. In this study the empirical correction suggested by Ahmed et al has been incorporated into the STTs to account for the back scatter [24].…”
Section: Back Scatter Correctionmentioning
confidence: 99%
“…The four beams in the treatment were simulated separately and MCDTK was used to evaluate a weighted sum of the doses, taking into account the number of monitor units per beam as well as the effect of backscatter from the secondary collimators (minimal, in this case, due to the backscatter plate) into the linear accelerator's monitor chamber [17,18]. MCDTK was then used to produce dose maps, isodose diagrams and cumulative dose volume histograms using the dose distributions from both the treatment planning system and the Monte Carlo simulations.…”
Section: B Monte Carlo Simulations and Dose Comparisonsmentioning
confidence: 99%